2004
DOI: 10.1021/jf0495136
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antioxidant Peptides from Fermented Mushroom Ganoderma lucidum

Abstract: Oxidative stress has been linked with the pathogenesis of many human diseases including cancer, aging, and atherosclerosis. The present study investigates the antioxidant activities of peptides isolated from the medicinal mushroom, Ganoderma lucidum. G. lucidum has been shown to possess potent antioxidant activity with little or no side effects. Polysaccharide, polysaccharide-peptide complex, and phenolic components of G. lucidum have been proposed to be responsible for this antioxidant effect. However, resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
122
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(144 citation statements)
references
References 43 publications
8
122
0
3
Order By: Relevance
“…(Yu-Hong et al, 2002;Zhang et al, 2003;Sun et al, 2004;Zhao et al, 2004;Chen et al, 2008;Jia et al, 2009;Li et al, 2009;Li et al, 2010;Li et al, 2011;Li et al, 2012a).…”
Section: Ganoderma Glycopeptidesunclassified
“…(Yu-Hong et al, 2002;Zhang et al, 2003;Sun et al, 2004;Zhao et al, 2004;Chen et al, 2008;Jia et al, 2009;Li et al, 2009;Li et al, 2010;Li et al, 2011;Li et al, 2012a).…”
Section: Ganoderma Glycopeptidesunclassified
“…Se-enrichment enhanced the concentrations of phenolics in comparison to the controls. It can be very important for human health, because some phenolic compounds, such as caffeic, protocatechuic, and p-coumaric acids, kaempferol, quercetin, and rutin, are excellent antioxidants (SUN et al, 2004;HAN et al, 2009). …”
Section: Phenolic Profi Lementioning
confidence: 99%
“…Another study reported that ethanolic extracts from the mushroom Coprinus comatus possessed higher antioxidant activity (47.0% at 20 µg/mL) than hot water extract [24]. A peptide obtained from another fermented mushroom (Ganoderma lucidum) showed inhibitory activities toward lipid peroxidation and lipoxigenase activity, which has been used to examine anti-inflammatory activity [25].…”
Section: Statistical Processingmentioning
confidence: 99%